Analysis of the Role of Health Integrated Post Cadres in Nutrition Services for Toddlers - Yolanda Putri; Mappeaty Nyorong; Nur’ Aini (Journal La Medihealtico, 2022)
Integrated Service Post or better known as POSYANDU is a means of empowering public health because the implementation model is activated and initiated by the community in line with the needs of each community. The purpose of this study was to determine the role of cadres and barriers to Posyandu cadres in nutritional services for toddlers in Ngijo Hamlet, Karangploso Community Health Center, Malang Regency. This research uses descriptive qualitative method. There were 10 informants in this study, consisting of 4 mothers with toddlers, 4 posyandu cadres, 1 health worker and 1 posyandu chairperson. Data analysis used descriptive qualitative and the validity of the data used was data triangulation. The results showed that the cadres had not fully implemented their role in nutritional services for children under five. The obstacle experienced by cadres is the lack of knowledge of cadres about posyandu, especially about malnutrition because they do not receive training. The conclusion in this study is that the role of posyandu cadres in nutritional services for children under five in Ngijo Hamlet, Karangploso Public Health Center, Malang Regency has not been implemented optimally. It is recommended to posyandu cadres and posyandu officers to further improve the knowledge and skills of posyandu cadres, especially in terms of nutrition for toddlers and increase counseling programs to mothers about posyandu and the benefits of implementing posyandu for mothers and toddlers.